The developmental consequences of early adverse care on infant macaques: A cross-fostering study. (December 2022) - McCormack, K.M.; Howell, B.R.; Higgins, M.; Bramlett, S.; Guzman, D.; Morin, E.L.; Villongco, C.; Liu, Y.; Meyer, J.; Sanchez, M.M.
Abstract: Early life adversity/stress (ELA/ELS), particularly adverse caregiving experiences such as child maltreatment (MALT), is a main risk factor for psychopathology, including psychiatric disorders such as anxiety, depression, ADHD, and substance abuse. Yet how these alterations unfold during development and the underlying mechanisms remain poorly understood, as it is difficult to prospectively and longitudinally study early developmental phases in humans, and nearly impossible to disentangle postnatal caregiving effects from heritable traits. This study examined the specific effects of "nurture" (maternal care) versus "nature" (heritable, biological maternal factors) on nonhuman primate infant socioemotional, stress neuroendocrine, and physical development. For this we used a translational and naturalistic macaque model of infant maltreatment by the mother with randomized assignment at birth to either mothers with a history of maltreating their infants (MALT group, n = 22) or to competent mothers (Control group, n = 20). Over the first 6 months of life (roughly equivalent to 2 years in humans), we examined the development of the mother-infant relationship, as well as infants' social behavior and emotional reactivity. In parallel, we assessed hypothalamic-pituitary-adrenal (HPA) axis function longitudinally, using measures of hair cortisol accumulation, and basal morning plasma cortisol. We identified broad impairments in maternal care exhibited by MALT foster mothers, beyond maltreatment (physical abuse, rejection) events, suggesting that MALT foster mothers provide an overall lower quality of care to their infants compared to Controls. MALT infants exhibited alterations in their initiations and breaks of proximity towards their mothers, as well as heightened emotional reactivity in comparison to Controls. Most striking are the HPA axis findings, with MALT infants showing higher levels of plasma cortisol across the first 6 postnatal months as well as higher hair cortisol accumulation from birth through month 6 (a signature of chronic stress) than Controls. No caregiving effects were detected on physical growth, which ruled out confounding effects of maternal nutrition, metabolism, etc. Taken together, these results suggest that the developmental trajectory of MALT and Control infants is different, marked by heightened levels of emotional reactivity, increased HPA activity and alterations in mother-infant interactions in MALT animals. These findings appear to be due to specific effects of postnatal maternal care, and not to biological/ behavioral traits inherited from the mother, or due to prenatal programming caused by prenatal stress, as the cross-fostering design controlled for these potential factors. However, we also detected a couple of interesting biological effects suggesting heritable transmission of some phenotypes. The prolonged HPA axis activation during the first 6 postnatal months of life is expected to have long-term consequences for brain, physiological, and behavioral development in MALT offspring. Highlights: Monkeys who were maternally maltreated demonstrate heightened emotional reactivity. Monkeys who were maternally maltreated exhibit higher levels of chronic stress. Maltreating mothers provide an overall lower quality of care to their infants.